THE ATTACK OF AL-SYIFA HOSPITAL IN THE REPORT OF ONLINE MEDIA REPUBLIKA, ALJAZEERA, AND BBC NEWS - Madinatul Munawwarah; M. Anwar Masadi; Lulu Eka Aprlilia (Balai Bahasa Nusa Tenggara Barat, 2024)
This article aims to reveal the exclusion and inclusion strategies and the differences in the use of reporting strategies onthe news of the Al-Syifa Hospital attack on Republika, Aljazeera, and BBC News online media using Van Luwen's critical discourse analysis theory. The type of research used is a qualitative method. Data sources are taken from Republika online news media entitled Pasukan Israel Kepung 3 Rumah Sakit di Gaza dan Mengebom kembali RS Al-Shifa, Aljazeera net entitled Al-Jazirah Nit Tarshadu Awdhaa'uhu, Hakadza Yabdu al-Mustasyfa al-Indunisiya bi Gazzah tahta al-Qashfi, and BBC News entitled “Israeli Militarry Looking into Reports of Gaza Hospital Blast”. The data were analyzed using descriptive analysis techniques, namely data presentation, data analysis, and conclusion drawing. The results showed that the news strategy used on Republika online media is an exclusion strategy with passivization and nominalization, and an inclusion strategy with differentiation, abstraction, nomination categorization, and nomination identification. Aljazeera uses exclusion strategies with passivization and nominalization techniques, as well as inclusion strategies with abstraction, nomination categorization and dissociation techniques. BBC News only uses exclusionary strategies with, passivization nominalization, and clause replacement techniques. The use of news strategies on Republika and Aljazeera media contrasts sharply with the use of strategies in the BBC News media, which only uses exclusion strategy. The use of these strategies shows that Republika and Aljazeera online media support Palestine, while BBC News online media support Israel.